2023
DOI: 10.1007/s00436-023-07787-6
|View full text |Cite
|
Sign up to set email alerts
|

The synergetic potential of Lactobacillus delbrueckii and Lactobacillus fermentum probiotics in alleviating the outcome of acute toxoplasmosis in mice

Abstract: Toxoplasmosis is an immunologically complex disease, particularly in immunocompromised patients. Although there are several therapeutic regimens for such disease, the majority of them have many drawbacks. Therefore, it is of utmost importance to improve the current regimen in an effort to achieve a well-tolerated therapy while also enhancing the host immune response. Famous for their immunomodulatory effect, Lactobacillus delbrueckii and Lactobacillus fermentum probiotics were chosen to be evaluated in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the parasites without treatment with 5-Ph-IAA, we observed that all the staining of markers were localized to the expected locations, and the differential interference constrast Fig. 4 Parasites depleted with SFA5 show pronounced phenotypic defects. Parasites of SFA5-mAID were grown in presence (+) or absence (-) of 5-Ph-IAA for 16 h, followed by IFA analysis using antibodies against markers (green) for the centriole (centrin1), the apicoplast (ACP), the endoplasmic reticulum (Bip), the cytoskeleton tubulin and the inner membrane complex (GAP45, IMC1 and MLC1).…”
Section: Sfa5 Is Involved In Formation Of Daughter Parasitesmentioning
confidence: 70%
See 1 more Smart Citation
“…In the parasites without treatment with 5-Ph-IAA, we observed that all the staining of markers were localized to the expected locations, and the differential interference constrast Fig. 4 Parasites depleted with SFA5 show pronounced phenotypic defects. Parasites of SFA5-mAID were grown in presence (+) or absence (-) of 5-Ph-IAA for 16 h, followed by IFA analysis using antibodies against markers (green) for the centriole (centrin1), the apicoplast (ACP), the endoplasmic reticulum (Bip), the cytoskeleton tubulin and the inner membrane complex (GAP45, IMC1 and MLC1).…”
Section: Sfa5 Is Involved In Formation Of Daughter Parasitesmentioning
confidence: 70%
“…Of interest is that all severity and pathology of toxoplasmosis originates from tissue destruction caused by the rapid replication cycle of the parasites and by lytic cycle in host cells. In this process, the parasite replication mechanism plays a core role in the maintenance of invasion capability [3][4][5].…”
Section: Introductionmentioning
confidence: 99%